The Potency of Seawater Battery with NiHCF + C Cathode Paired to Wind Turbine for Generating Clean Electricity in Rural Area - Fadhillah Raka Pratama; Alfi Gymnastiar Pratama; Beta Maisaroh (NBRI Press, 2023)
Electricity supply becomes the main issue in every country, because most of them are not distributed well. Electricity deficit potentially threatens the society and hampers the economic growth due to lack of power capacity. At the same time, many areas has untapped renewable sources that possibly fulfill the electricity demand. In fact, renewable energy (RE) is more environmentally friendly compared to fossil fuels power plant. However, the RE intermittency remains a problem. The most promising solution comes from RE storage, one of them are seawater battery. Besides it does not depend on heavy metal extraction, in which claimed safer, seawater also has a maximum power density and more effective voltage efficiency. The utility of seawater battery possibly will be used as RE storage on wind turbines system in rural area so-called 3T. In this study, seawater battery applies NiHCF cathode. NiHCF intercalation of sodium is synthesized using a gellatic method. NiHCF is smoothed and blended with polyvinylidene fluoride and black carbon at 3.5 milliliters 1-metil-2-pyrrolidone. The NiHCF cathode has an advantage of a voltage discharge with a 60-86% range. Compared with RO battery, seawater battery have nearly twice as much efficiency as RO battery. It is also known in previous research that NiHCF cathode has a capacity at 75 kW. The seawater battery is composed in a three-part battery pack, namely C1, C2, and C3. The separator that is used between C1 and C2 is AEM, while between C2 and C3 is NASICON. Electricity flows from wind turbines that generates electricity and streams to the battery pack, then distributes to the user.